Influence of Cypermethrin on DNA and RNA Content in Different Organs of Fresh Water Fish Cyprinus carpio: Effect of Cypermethrin on DNA and RNA in Fishes - Balaji Gowri; Venugopal Ramalingam; Palaniandy Govindassamy (Iranian Journal of Pharmaceutical Sciences, 2013)
In this study, freshwater fish Cyprinus carpio was exposed to sub lethal concentration of synthetic pyrethroids insecticide cypermethrin to evaluate the impact on nucleic acids in different organs. Fishes were exposed to sub lethal concentration (1/10th of LC50 value) of cypermethrin for three different durations, 7, 14 and 21 days. In seven day exposed fishes, DNA and RNA contents were not altered by cypermethrin. Whereas in 14 day and 21 day exposed fishes the DNA and RNA content decreased significantly in brain, gills and liver. However, the decrease was more in 21 day exposed fishes. The reduction in the DNA and RNA content in cypermethrin exposed fishes is comparatively less in liver when compared to the brain and gills. Cypermethrin treatment diminished RNA/DNA ratio in all the fish organs tested. In all the three organs studied, the influence of cypermethrin was found to be exposure time dependent.